Construction of Complex Lattice Codes via Cyclotomic Fields
Through algebraic number theory and Construction A we extend an algebraic procedure which generates complex lattice codes from the polynomial ring F_2[x]/(x^n-1), where F_2={0,1}, by using ideals from the generalized polynomial ring F_2[x,12Z_0]((x^12 )^n-1) through the ring of integers O_L of the cyclotomic field L=Q(ζ_2^s ), where ζ_2^s is a 2^s-th root of the unit, with s>2., number=1, journal=Trends in Computational and Applied Mathematics, author=Carvalho, E. D. and Andrade, A. A. and Shah, T. and Trinca, C. C., year=2022, month=Mar., pages=33–50